Menyimak Relasi Kekuasaan Dalam Kartun - Ahmad, Munawar (Jurnal Ilmu Sosial dan Ilmu Politik, 2001)
As a main medium for political struggle, cartoon contains a well-designed apparatus for conveying set of messages. The usesage of semiotics and critical discourse analysis allows us to uncover its political design. This article demonstrates the usage of those analytical tool to scrutinize an episode of Panji Koming cartoon serial from the daily Kompas.